The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1074/jbc.m203041200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Monocyte Cyclooxygenase-2 Gene Expression by Human Herpesvirus 6

Abstract: Prostaglandin E 2 (PGE 2 ) is an arachidonic acid metabolite mainly produced by activated monocytes/macrophages (Mo/M) that display broad immunomodulatory activities. Several viruses capable of infecting Mo/M modulate PGE 2 synthesis in a way that favors the infection processes and the spread of virions. In the present work, we studied the effect of human herpesvirus 6 (HHV-6) infection of Mo/M on PGE 2 synthesis. Our results indicate that HHV-6 induces COX-2 gene expression and PGE 2 synthesis within a few ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 98 publications
2
18
0
Order By: Relevance
“…4). This finding is consistent with previous evidence that AP-1 mediates the induction of COX-2 by a variety of stimuli (10,(21)(22)(23)(24). ChIP analysis indicated that HDAC inhibitors blocked PMA-mediated induction of COX-2 by suppressing the binding of c-Jun to the COX-2 promoter.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…4). This finding is consistent with previous evidence that AP-1 mediates the induction of COX-2 by a variety of stimuli (10,(21)(22)(23)(24). ChIP analysis indicated that HDAC inhibitors blocked PMA-mediated induction of COX-2 by suppressing the binding of c-Jun to the COX-2 promoter.…”
Section: Discussionsupporting
confidence: 83%
“…Oncogenes, growth factors, cytokines, and tumor promoters stimulate COX-2 transcription via protein kinase C and RAS-mediated signaling (5)(6)(7)(8)(9)(10). Depending on the stimulus and cell type, a variety of transcription factors including activator protein-1 (AP-1) can stimulate COX-2 expression (21)(22)(23). Recently, the histone acetyltransferase activity of the CREB-binding protein/p300 co-activator complex was found to be important for AP-1-mediated induction of COX-2 (24).…”
mentioning
confidence: 99%
“…Viral infections often induce the synthesis of elevated levels of inflammatory mediators, including COX-2, that may alter the functions of the infected cells (25). COX-2 is one of the most important inflammation mediators being the target of nonsteroidal anti-inflammatory drugs (48).…”
Section: Discussionmentioning
confidence: 99%
“…One such secreted product released is prostaglandin E 2 (PGE 2 ) that is a strong lipid mediator of inflammation and modulator of the immune response. Recent evidence shows that many viruses have been linked to the regulation of COX-2 expression and the production of prostaglandins (PGs) (25)(26)(27). Viruses that interact with Mo/M efficiently modulate the synthesis of PGE 2 (28,29).…”
mentioning
confidence: 99%
“…In human herpes virus 6 (HHV-6) infected human monocytes/macrophages, COX-2 gene promoter activity increases 22-fold compared to mock-infected cells [49]. HHV-6 encoded IE2, but not HHV-6 IE1 protein, also activates the COX-2 promoter.…”
Section: Introductionmentioning
confidence: 98%